2014
DOI: 10.1073/pnas.1408741111
|View full text |Cite
|
Sign up to set email alerts
|

Entrained neural oscillations in multiple frequency bands comodulate behavior

Abstract: Our sensory environment is teeming with complex rhythmic structure, to which neural oscillations can become synchronized. Neural synchronization to environmental rhythms (entrainment) is hypothesized to shape human perception, as rhythmic structure acts to temporally organize cortical excitability. In the current human electroencephalography study, we investigated how behavior is influenced by neural oscillatory dynamics when the rhythmic fluctuations in the sensory environment take on a naturalistic degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
212
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(235 citation statements)
references
References 60 publications
22
212
0
1
Order By: Relevance
“…Evidence supporting this possibility in human studies shows that the phase of entrained or cross-modally reset cortical oscillations can have subtle effects on auditory perception (24,45,46), behavioral response times (26), and visual detection thresholds (23,40,47,48). Previous work has also shown both that the degree of multisensory perceptual binding is modulated by stimulus type (5), task (49), and prior experience (50), and that oscillatory entrainment adjusts as a function of selective attention to visual or auditory stimuli (51,52).…”
Section: Discussionmentioning
confidence: 94%
“…Evidence supporting this possibility in human studies shows that the phase of entrained or cross-modally reset cortical oscillations can have subtle effects on auditory perception (24,45,46), behavioral response times (26), and visual detection thresholds (23,40,47,48). Previous work has also shown both that the degree of multisensory perceptual binding is modulated by stimulus type (5), task (49), and prior experience (50), and that oscillatory entrainment adjusts as a function of selective attention to visual or auditory stimuli (51,52).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies in the auditory domain had localized the origin of the low-frequency activity to sensory areas and not frontal regions (13,14,35) but were confounded by the presentation rate, which likely evoked activity (14,35,36). Given that exogenous stimulation induces a strong phase alignment (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It has been argued that lowfrequency neuronal oscillations might reflect a cortical mechanism for sensory selection, attentional allocation, and evidence updating during decision making (9,11,13,14,32). If the underlying functional brain architecture is inherently rhythmic, then we should be able to observe rhythmic patterns in behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that detection performance varied as a function of phase lag and that this function resembled well the tACS waveform. Henry (2012;Henry et al 2014) used a periodic 3-or 5-Hz modulation applied to an interrupted tone carrier as entraining stimulus. They manipulated the relative timing of the gap and the ongoing modulation and found that this influences gap detection in the phase-dependent manner described above for the tACS study.…”
Section: Cortical Oscillatory Phase Influences Auditory Perceptionmentioning
confidence: 99%